Assessment of Parents and Teachersâ€™ Attitude towards Sexuality Education as a Subject in Nigerian Secondary Schools - Egharevba, John; Okunzuwa, Uzamere Razaq (NIU Journal of Humanities; Vol 6 No 3 (2021): KIU Journal of Humanities, Vol. 6 No. 3, September 2021, 2021)
The study investigated the assessment of parents and teachersâ€™ attitude towards sexuality education as a subject in Nigerian Secondary schools. The survey research method was adopted. The sample for the study consisted of 400 teachers and parents selected from Edo South Senatorial District in Edo State. The research instrument was a questionnaire titled: â€œAssessment of Parents and Teachers Attitude of Sexuality Educationâ€. Data collected was analyzed using the disproportionate stratified random sampling technique. Analyses of data revealed among others that teachers and parents have a good attitude about sexuality education as a subject in Nigerian secondary schools. Based on the findings, it was recommended among others that sexuality education should be introduced in schools early enough. Since both parents and teachers are understandably disposed to sexuality education, public enlightenment should be carried out to improve on public attitude towards sexuality education. Keywords: Parents, Teachers, Attitude, Sexuality Education, Secondary Schools